A COMPARATIVE TRIAL OF COPPER T 380 AND Cu 375 IUCD - Khan, Shazia A; Amin, Zain Ul; Fouzia, Fouzia; Jadoon, Samina (Journal of Ayub Medical College Abbottabad, 2010)
Background: The IUCD, primarily in the form of copper IUD is used by more than 150 million women around the world, making it the most widely used reversible method of contraception. The objective of this study is to do double blind clinical trial to compare the side effects of Copper-T and Cu 375 IUCD in women using contraceptive method and had used no contraception before. Method: A total of 80 women of reproductive age group who are sexually active and who wanted to practice some contraceptive method were included in the study. After filling Performa speculum examination was also done and all the contra indications for the fitting of IUCD were ruled out. Results: In this comparative study the effectiveness and side effects of two copper releasing IUCDs, Copper-T and Cu 375 IUCD was observed. Pelvic inflammatory disease occurred more often with Cu 375 IUCD than other group. Dysmenorrhoea was also experienced more with Cu 375 IUCD user than Copper-T. Menorrhagia rate was also high in Cu 375 IUCD users. The only case of uterine perforation was in the user of Copper-T. Conclusion: It is concluded from this study that Copper-T is a highly effective method of contraception than Cu 375 IUCD with good patient acceptance and lesser side effects. Keywords: Contraception, expulsion, PID